MINUMAN TINGGI AKTIVITAS ANTIOKSIDAN BERBAHAN DASAR ALAMI MINYAK BEKATUL PADI (Oryzae sativa) DAN EKSTRAK MENIRAN (Phyllanthus niruri) - Purnawati Hustina Rachman; Priskila Priskila; Evy Damayanthi; Bambang Pontjo Priosoeryanto (Food and Nutrition Society of Indonesia, 2012)
This study aimed to assess the antioxidant potential of chocholate-rice bran oil-emulsion beverage and meniran extract beverage. RBO beverage was made using oil in water emulsion with sugar ester as the emulsifier.Four formulas was created with the RBO-chocolate concentrate : water ratio of 1:1, 1:3, 1:5, and 1:7. Meanwhile the meniran beverage was made by adding extract meniran in five different concentrations (30, 40, 50, 60, 70 ppm) along with flavor and sucralose. The selected emulsion beverage had the AEAC value of 30.75 mg Vit C/100 g, while the meniran extract beverage had the AEAC value of 9.12 mg Vit C/100 g with the total fenol of 92.75 mg/100 g. The results of TBA value, content of protein, fat, carbohydrate, ash, and water of the emulsion beverage were 0.12 mg malondialdehyde eq/kg, 0.24%, 0.52%,6.74%, 0.15% and 92.32%, respectively. Increasing concentrations of chocolate and RBO significantly affected the results of the chemical parameters (p<0.05). Overall, the chocolate emulsion beverage based on RBO and meniran extract beverage had high antioxidant activity that are potential to prevent non-communicable diseases.